MSMEs SUPPLY CHAIN STRATEGY OPTIMIZATION - Aprilia, Hani Damayanti (Jurnal Kompetitif Bisnis, 2021)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia have a very important role in the economy, and have great potential to increase their role in exports. Lampung Province has considerable potential for MSME products. One of them is banana chips MSMEs. In a business, the supply chain is very important, where the availability and distribution of goods will greatly affect the sustainability of a business. This study aims to develop an optimal supply chain strategy model for Banana Chips MSMEs in Bandar Lampung. Data analysis used an interactive model developed by Miles & Huberman. The results showed that the supply chain activities of Banana Chips MSMEs in Bandar Lampung included product development, material procurement, production and supply, distribution and marketing, as well as consumers. Banana Chips MSMEs in Lampung still apply the traditional supply chain system. Thus, an optimal alternative supply chain model is developed so that MSMEs can compete in the global era, by developing a wider marketing channel and distribution.